The Influence of Bullying on The Development of Self-Confidence of Grade 4 Students at Elementary School 1 Gondanglegi - Anisa, Sarah; Mardhatillah, Mardhatillah; Persada, Yuris Indria (Jurnal Ilmiah Teunuleh, 2024)
Bullying is rehashed forceful behavior that's intentioned done to harmed, mortify, or rule others physically, candidly, or rationally. There are numerous cases of bullying, particularly in Indonesia where 35% of them happen in schools, due to a few variables that cause it as well as the moo level of self-confidence of Indonesian children. This consider points to look at the impact between bullying on the advancement of self-confidence in understudies, particularly in review IV children at SDN 1 Gondanglegi. This investigate was conducted utilizing quantitative strategies by dispersing surveys to respondents who fit the investigate test criteria. The comes about appeared: 1) From the comes about of typicality test, it is gotten that the contrast between the watched information is typical. 2) From the comes about of relationship test gotten between bullying and the improvement of self-confidence is modestly connected with a positive relationship. 3) From the comes about of basic direct relapse investigation, it is gotten that bullying does not completely influence the advancement of students' self-confidence, and the coefficient of assurance is 32%. In this way, it is concluded that bullying does not completely influence the level of students' self-confidence.